Empowerment and engagement of SHGs against RTI/STI in Karnataka, India: an interventional study - Gupta, Manoj Kumar; RS, Reshmi; Kumar, Dhirendra; Visengrawala, Fehmida (International Journal of Research in Medical Sciences, 2017)
Background: Reproductive Tract Infections (RTIs) including Sexually Transmitted Infections (STIs) are ‘silent’ epidemics and are recognized as public health problem and rank second as the cause of healthy life lost among women of reproductive age after maternal morbidity and mortality in developing countries. Development and use of IEC material along with active participation by the community ensures delivery of appropriate information and knowledge to people which in turn empowers them to make informed decisions about their health. Methods: This was a ‘Multi-centric action research demonstration study’ to empower and engage the Self Help Groups (SHGs) women by creating awareness and sustaining interest through lesson plans in the IEC material regarding prioritized problem, required interventions and their access for syndromic recognition of the RTI/STIs. As an intervention, series of workshops were conducted with the help of pre-developed IEC material. 400 households (200 from each intervention and control sites) of SHG women were interviewed for baseline and endline each. Results: Intervention was found effective in the form of a significant improvement in the level of awareness about RTI/STI, correct knowledge about white discharge, capability to identify the symptoms of RTI/STI and health seeking behavior of the respondents. Conclusion: This study provides experience of the feasibility, efficacy and impact of health education interventions and point out that cost-effective strategies for prevention of RTI/STI are needed through information, education, and behavior change.